Supporting pupils with autistic spectrum disorders : a guide for school support staff - Plimley, Lynn (Autistic spectrum disorders support kit., 2006)
When a young person with autistic spectrum disorders enters secondary school, there are lots of new factors to consider. This books looks at: "making good transitions from primary school. "how to provide helpful INSET for teachers, senior managers, support staff and lunchtime supervisors. "using the young person's special interest as a tool for learning. "record-keeping, IEPs and sharing information across the school. "subject disapplication and formal examinations. "social strategies to employ in a large high school. "useful tips for staff - what to do and w